Subject, Definition, Activity Framing Avicenna's Science of the Soul - Alpina, Tommaso (Scientia Graeco-Arabica ;, 2021)
This book offers for the first time a comprehensive study of the reception and reworking of the Peripatetic theory of the soul in the Kitāb al-Nafs (Book of the Soul) by Avicenna (d. 1037). This study seeks to frame Avicenna's science of the soul (or psychology) by focusing on three key concepts: subject, definition, and activity. The examination of these concepts will disclose the twofold consideration of the soul in Avicenna's psychology. Besides the 'general approach' to the soul of sublunary living beings, which is the formal principle of the body, Avicenna's psychology also exhibits a 'specific orientation' towards the soul in itself, i.e. the human rational soul that, considered in isolation from the body, is a self-subsistent substance, identical with the theoretical intellect and capable of surviving severance from the body. These two investigations demonstrate the coexistence in Avicenna's psychology of a more specific and less physical science (psychologia specialis) within a more general and overall physical one (psychologia generalis).